Performance Analysis of Convert a Gray Image to Color Image - P, Ravi (International Journal of Computer Sciences and Engineering, 2019)
A simple and efficient method for coloring the gray-scale images into the color images with the existing color map or with creating a new one. The conversion of grayscale images into the color images using different algorithm methods. This color matching technique helps in adding chromatic values to a colorless image and measure for color transfer. Moderately than choosing the entire color from the source to the target image transfer RGB colors from a palette to color gray scale components, by matching difference information between the images. The target image achieved high quality with higher PSNR and lower MSE metrics. It shows that this simple method can be successfully applied to a variety of gray scale images and it can be applicable in different applications.